5G radio access network architecture : the dark side of 5G - Sirotkin, Alexander, 1975- (Hoboken, NJ, USA : Wiley-IEEE Press, 2020)
"Written by an industry insider with state of the art research at their fingertips, this book describes the Radio Access Network (RAN) architecture, starting with currently deployed 4G, followed by the description of 5G requirements and why re-thinking of the RAN architecture is needed to support these. Based on these considerations, it explains how 5G network architecture, which is currently being defined, is likely to evolve. The aim is not merely to cover relevant standards and technologies as a purely academic exercise (although a significant part of the book will be dedicated to these), but to augment these by practical deployment, to illustrate why the RAN architecture is changing and where it is going. With 5G deployments on the horizon, there is a desire within companies to both re-think the RAN architecture and to change the proprietary nature of the RAN. Correspondingly, there is increased interest in academia, standards bodies and commercial entities involved in the area"-- Provided by publisher
Market Drivers / Reza Arefi, Sasha Sirotkin -- 5G System Overview / Sebastian Speicher, Sasha Sirotkin, Sudeep Palat, Alexei Davydov -- NG-RAN Architecture / Colby Harper, Sasha Sirotkin -- NG-RAN Evolution -- Enabling Technologies -- NG-RAN Deployment Considerations / Andreas Neubacher, Vishwanath Ramamurthi
BIBINDX
Keywords: 5G mobile communication systems; Computer network architectures; Electronic books